How the marketing research affects the improvement in the dental doctor-patient relation - GEANGU, Petronela Iuliana; GÂRDAN, Daniel Adrian; CETINĂ, Iuliana; GURGU,, Elena (Annals of Spiru Haret University. Economic Series, 2010)
The relation between provider and customer in the services area, mainly medical, represents a fundamental desideratum. This type of relation derives from a two-way involvement of both parts at the entire marketing mix level. The base of new marketing strategies that imply effective relation models can only be built by setting out an ample time related investigation process of the mechanisms pertaining to the customer’s perception of the quality and the coordinates of the relationship with the provider. The article aims to investigate the mechanism leading to customer retention in the case of dental offices, both from the perspective of customers and providers. The authors conducted an in-depth interview-type qualitative research, which identified and pointed out the extent to which the marketing activity, as seen from the perspective of specific principles and scientific methodology, is implemented in the dental offices in Bucharest. The research was also focused on the perception of specialists, dental office/clinics managers or owners regarding the concept of customer retention, elements which could lead to keeping customers, and the image of the ideal office from the perspective of services adjusted to consumers.